The significance of wing and body morphometry in discriminating of Six Eurema butterflies (Lepidoptera: Pieridae) of Peninsular Malaysia - Azrizal-Wahid, N.; Sofian-Azirun, Mohd; Rizman-Idid, M. (Penerbit Universiti Kebangsaan Malaysia, 2016)
Six species of Eurema butterflies comprised of 261 adult individuals collected from various sampling sites in Peninsular Malaysia were identified. The morphometric measurement of the specimens was carried out by using seven characters measured from the wing and body regions. Morphometric analysis was determined through the multivariate analysis of Discriminant Function Analysis (D FA) and Cluster Analysis. The results of D FA showed that two out of seven characters utilized have the lowest values of Partial's Wilks Lambda; basal length and hindwing length. These characters therefore are significant for the discrimination of the Eurema species. The classification matrix shows that both E. hecabe and E. blanda were completely discriminated by the characters set. Moreover, there was great overlaps occurred between the species groups when plotting a conical graph except for species E. blanda that formed homogenous group. Basal length was also suggested as the species-specific character for grouping the species E. blanda. In Cluster Analysis, E. hecabe tends to be closer to E. sari with the lowest value of agglomeration. The results from dendogram generated from average linkage also showed several relationship patterns among the six species.